Ecological sustainability in investment-State dispute settlement: risks of legal pluralism in practice - Bas Vilizzio, María Magdalena (2021)
Due to the fragmentation of International Law, Investor-State dispute settlement is usually an area in which tension are felt between investment protection and public policy space, especially in matters concerning the environment, public health or human rights. This tension is even more dangerous in health emergencies, such as the covid-19 syndemic, and has a deeper impact on low and middle-income countries. In light of the above, this article aims to identify and analyse three investor-State disputes involving low and middle-income countries, in which the collision between investment protection and ecological sustainability sets of norms evidences the risks of legal pluralism in International Law.